Trust-based access control model with quantification method for protecting sensitive attributes - Salji, Mohd Rafiz; Udzir, Nur Izura; Hafez Ninggal, Mohd Izuan; Mohd Sani, Nor Fazlida; Ibrahim, Hamidah (The Science and Information Organization, 2022)
The prevailing trend of the seamless digital collec-tion has prompted privacy concerns to the organization. In enforc-ing the automation of privacy policies and laws, access control has been one of the most devoted subjects. Despite the recent advances in access control frameworks and models, there are still issues that hinder the implementation of successful access control. This paper illustrates the problem of the previous model which typically preserves data without explicitly considering the protection of sensitive attributes. This paper also highlights the drawback of the previous works which provides inaccurate calculation to specify user’s trustworthiness. Therefore, a trust-based access control (TBAC) model is proposed to protect sensitive attributes. A quantification method that provides accurate calculation of the two user properties is also proposed, namely: seniority and behaviour to specify user’s trustworthiness. Experiment have been conducted to compare the proposed quantification method and the previous quantification methods. The result shows that the proposed quantification method is stricter and accurate in specifying user’s trustworthiness as compared to the previous works. Therefore, based on the result, this study resolves the issue of specifying the user’s trustworthiness. This study also indicates that the issue of protecting sensitive attributes has been resolved.